America the beautiful : rediscovering what made this nation great - Carson, Ben. (Grand Rapids, Mich. : Zondervan, 2012)
What is America becoming? Or, more importantly, what can she be if we reclaim a vision for the things that made her great in the first place? In America the Beautiful, Dr. Ben Carson helps us learn from our past in order to chart a better course for our future. From his personal ascent from inner-city poverty to international medical and humanitarian acclaim, Carson shares experiential insights that help us understand: what is good about America; where we have gone astray; which fundamental beliefs have guided America from her founding into preeminence among nations. Written by a man who has experienced America's best and worst firsthand, America the Beautiful is at once alarming, convicting, and inspiring. You'll gain new perspectives on our nation's origins, our Judeo-Christian heritage, our educational system, capitalism versus socialism, our moral fabric, healthcare, and much more. An incisive manifesto of the values that shaped America's past and must shape her future, America the Beautiful calls us all to use our God-given talents to improve our lives, our communities, our nation, and our world. - Publisher.
Tackling the issues at the forefront of the American mind--healthcare, education, capitalism, and more America the Beautiful is indispensable reading. From four-time bestselling author, internationally renowned neurosurgeon, and humanitarian Dr. Ben Carson, here is a sobering and inspiring manifesto of America's greatness, her failings, and the values and changes it will take to carry our country into a brilliant and prosperous future.
America's history of rebelling for change -- Who are "we the people"? -- Are we a Judeo-Christian nation or not? -- A different school of thought -- Capitalism: its pros and cons -- Socialism: whose pot of soup is it? -- What is a moral nation? -- Learning from our mistakes -- America's role in a world at war -- Is health care a right? -- A nation divided -- Liberty and justice for all -- What's good about America? -- What do we believe and in whom do we trust?
Includes bibliographical references (pages 199-205).
Keywords: United States -- Civilization; Social values -- United States; United States -- Politics and government -- 21st century; Civilization; Political science; Social values; United States; United States -- Civilization; Social values -- United States; United States -- Politics and government; 2000 - 2099